Control of airborne infectious disease in buildings: Evidence and research priorities. (24th November 2021) - Bueno de Mesquita, P. Jacob; Delp, William W.; Chan, Wanyu R.; Bahnfleth, William P.; Singer, Brett C.
Abstract: The evolution of SARS‐CoV‐2 virus has resulted in variants likely to be more readily transmitted through respiratory aerosols, underscoring the increased potential for indoor environmental controls to mitigate risk. Use of tight‐fitting face masks to trap infectious aerosol in exhaled breath and reduce inhalation exposure to contaminated air is of critical importance for disease control. Administrative controls including the regulation of occupancy and interpersonal spacing are also important, while presenting social and economic challenges. Indoor engineering controls including ventilation, exhaust, air flow control, filtration, and disinfection by germicidal ultraviolet irradiation can reduce reliance on stringent occupancy restrictions. However, the effects of controls—individually and in combination—on reducing infectious aerosol transfer indoors remain to be clearly characterized to the extent needed to support widespread implementation by building operators. We review aerobiologic and epidemiologic evidence of indoor environmental controls against transmission and present a quantitative aerosol transfer scenario illustrating relative differences in exposure at close‐interactive, room, and building scales. We identify an overarching need for investment to implement building controls and evaluate their effectiveness on infection in well‐characterized and real‐world settings, supported by specific, methodological advances. Improved understanding of engineering control effectiveness guides implementation at scale while considering occupant comfort, operational challenges, and energy costs.